Subchronic toxicity evaluation of the extract from endophytic Bacillus sp. DO-R5 in a mice model - Trần, Chí Linh; Nguyễn, Trọng Tuân; Đái, Thị Xuân Trang (Hue University Journal of Science: Natural Science, 2026)
Endophytic bacteria isolated from medicinal plants are emerging as a valuable source of bioactive compounds with therapeutic potential. In this study, we evaluated the sub-chronic toxicity of the ethyl acetate extract from Bacillus sp. DO-R5 (BaDO-R5) (gene bank accession number PQ533190), an endophytic strain isolated from the root of Dillenia ovata, a native medicinal plant. The extract was administered orally to mice at a daily dose of 400 mg/kg/day for 45 and 90 consecutive days. Throughout the study, behavioral and physiological parameters were closely monitored. At the end of the treatment periods, the body weight gain, organ-to-body weight ratios, hematological indices, biochemical markers (including liver enzymes, kidney function, glucose, and lipid profiles), and gross morphology of the liver, kidneys, and spleen were assessed. Results indicated that BaDO-R5 did not induce abnormal behaviors or mortality. Organ morphology remained normal, and no significant changes were observed in hematological or biochemical parameters. Liver and kidney function markers, including SGOT, SGPT, urea, and creatinine, stayed within normal ranges. Importantly, cardiovascular risk indicators such as AIP, AC, and CRR were not adversely affected. The results showed that the BaDO-R5 extract did not cause significant toxicity in the sub-chronic toxicity study, contributing to the preclinical safety data and suggesting potential for further studies.